1993
DOI: 10.1063/1.353446
|View full text |Cite
|
Sign up to set email alerts
|

Silicide formation and silicide-mediated crystallization of nickel-implanted amorphous silicon thin films

Abstract: The nucleation and growth of isolated nickel disilicide precipitates in Ni-implanted amorphous Si thin films and the subsequent low-temperature silicide-mediated crystallization of Si was studied using in situ transmission electron microscopy. Analysis of the spatial distribution of the NiSi2 precipitates strongly suggested the occurrence of site saturation during nucleation. NiSi2 precipitates were observed in situ to migrate through the amorphous Si thin films leaving a trail of crystalline Si at temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
251
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(254 citation statements)
references
References 26 publications
3
251
0
Order By: Relevance
“…We attribute such reverse annealing phenomenon to the effects of nickel silicide mediated crystallization of the amorphous Si zones within the Ni implanted region. The nickel silicide precipitates formed during annealing can act as heterogeneous nucleation sites for displaced Si atoms to recrystallize; and as the silicide precipitates migrate, a trail of Si crystallites of needle-like morphology forms within the matrix, 19 which is also confirmed by our HRTEM morphology (Fig. 2(d)).…”
Section: Resultssupporting
confidence: 65%
“…We attribute such reverse annealing phenomenon to the effects of nickel silicide mediated crystallization of the amorphous Si zones within the Ni implanted region. The nickel silicide precipitates formed during annealing can act as heterogeneous nucleation sites for displaced Si atoms to recrystallize; and as the silicide precipitates migrate, a trail of Si crystallites of needle-like morphology forms within the matrix, 19 which is also confirmed by our HRTEM morphology (Fig. 2(d)).…”
Section: Resultssupporting
confidence: 65%
“…Given the proposition that MILC is an "interfacial" process mediated by Ni diffusion across NiSi nodules at the crystallization front [4], [19], it is not surprising that neither Ni diffusion across the MILC region nor its diffusion into the a-Si region are the rate controlling steps in MILC. Interestingly, the MILC values extracted from the two different kinds of substrates, while significantly different from the 1.55 eV for NiSi formation and the 2.9 eV for NiSi degradation [20], are much closer to the value of 2.08 eV for Ni induced lateral secondary grain growth in poly-Si reported by Hong et al [20] and the 1.9 eV for Au induced poly-Si recrystallization reported by Allen et al [21]-who suggested that the activation energy could be attributed to the energy required to attach a Si atom to the growing crystallization front.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of excess metallic Ni at the bottom of the stack was attributed to the diffusion of the NiSi 2 nodules. Hayzelden et al (Hayzelden & Batstone, 1993) reported an in-situ transmission electron microscopy study on Ni induced aSi crystallization and suggested a similar mechanism for the diffusion of NiSi 2 in a-Si matrix. According to the mechanism proposed by these authors, Si first crystallizes on one of the eight faces of NiSi 2 crystalline seeds and then it dissociates as Ni and Si atoms at the c-Si/ NiSi 2 interface.…”
Section: Metal Induced Lateral Crystallization (Milc)mentioning
confidence: 99%